Analisis faktor keputusan ibu bersalin dalam pemilihan tempat pelayanan persalinan di wilayah kerja Puskesmas Ulee Kareng Kota Banda Aceh - Hastuti Syahnita; Sri Rahayu; Defriman Djafri (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Choosing a place of birth is not an easy thing for a mother, because a safe and comfortable place has a positive impact in launching the birth process.Objective: This study analyzes the factors of choosing a delivery service in Ulee Kareng health center area Banda Aceh City.Methods: This research is an analytic type of research using a cross-sectional design. Population The population in this study were all mothers giving birth with normal delivery in the working area of the Ulee Kareng Health Center in 2016 as many as 389 people. Data were collected by interview using a questionnaire. Interviews were conducted directly on the respondents. Data analysis using Chi-square test.Result: The results have shown that the factors related to the choice of place of delivery service are education level (p= 0.007), occupation (p= 0.014), income level (p= 0.000), history of childbirth (p= 0.019), and family support factors. (p= 0.004) and support from health workers (p= 0.007).Conclusion: The choice of place of delivery is influenced by the level of education, occupation, income, birth history, as well as family support and health workers. While the most dominant factor is the level of family income.